United States strategic interests in Latin America : an assessment. - COLL, Albert R. (1997)
Discusses the three areas of strategic interest of the US in Latin America, viz: military, economic and political. Notes that the marked improvement in US-Latin American relations over the past decade, and the overall reduction in the number and scale of serious challenges to US military, economic and political interest should not obscure some long-term, structural concerns, especially in the conomic and political arenas.